Analysis of Consumer Satisfaction of Ornamental Fish in Palembang City (Palembang Bird Market Case Study) - Manik, Grace Sondang Rona Tama; Suryana, Asep Agus Handaka; Yustiati, Ayi; Nurhayati, Atikah (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
This research aims to analyze the level of consumer satisfaction at the Palembang Bird Market and analyze the main variables that greatly influence the level of consumer satisfaction. Data collection and processing will be carried out in September – October 2023 in Palembang City. The research method used is the case study method, with a sampling technique namely purposive sampling. The data analysis used is the Customer Satisfaction Index (CSI). The results of this research showed that the Customer Satisfaction Index (CSI) value was 76.89% in the satisfied category. The variable with the highest level of satisfaction is the product quality variable for ornamental fish health attributes with a Mean Satisfaction Score (MSS) of 4.46. The variable that has the lowest level of satisfaction is the shop atmosphere variable on the shop cleanliness attribute with a Mean Satisfaction Score (MSS) of 2.89. The main variable that most influences satisfaction by looking at the level of importance is the product quality variable on the attributes of variations and types of ornamental fish with a Mean Importance Score (MIS) value of 4.76.